The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/etc.1822
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation kinetics of arsenic in Daphnia magna under different phosphorus and food density regimes

Abstract: In the present study, the dissolved uptake, dietary assimilation, and elimination of arsenic (initially added as arsenate) in the freshwater cladoceran Daphnia magna were examined. A biphasic correlation between the arsenic uptake rate and its ambient concentration, as well as a two-saturation-site arsenic uptake competition with phosphate was observed. The calculated uptake rate constant, as influenced by the ambient phosphorus concentration, ranged from 0.035 to 0.35 L/g/d. Food concentration substantially d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 45 publications
1
38
1
Order By: Relevance
“…Moreover, a favorable environment, rich in nutrients, could promote the formation of detoxifying agents, such as metallothionein, binding to arsenic ions, which makes this ametal unavailable (Miao et al 2012). For many authors, metallothioneins are produced in situations of stress, such as contamination by metals, and play a key role in reducing toxicity of selenium, cadmium, zinc, copper, silver and arsenic among others (Cousins 1983, Kägi and Schäffer 1990, Roesijadi 1992, Amiard et al 2006, Tsui and Wang 2007, Nordberg and Nordberg 2009, Miao et al 2012.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, a favorable environment, rich in nutrients, could promote the formation of detoxifying agents, such as metallothionein, binding to arsenic ions, which makes this ametal unavailable (Miao et al 2012). For many authors, metallothioneins are produced in situations of stress, such as contamination by metals, and play a key role in reducing toxicity of selenium, cadmium, zinc, copper, silver and arsenic among others (Cousins 1983, Kägi and Schäffer 1990, Roesijadi 1992, Amiard et al 2006, Tsui and Wang 2007, Nordberg and Nordberg 2009, Miao et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…For many authors, metallothioneins are produced in situations of stress, such as contamination by metals, and play a key role in reducing toxicity of selenium, cadmium, zinc, copper, silver and arsenic among others (Cousins 1983, Kägi and Schäffer 1990, Roesijadi 1992, Amiard et al 2006, Tsui and Wang 2007, Nordberg and Nordberg 2009, Miao et al 2012. Bodar et al (1990) reported a temporary cadmium tolerance in Daphnia magna by the production of metallothionein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations